Combination Calcium Hydroxide and Epigallocatechin-3-gallate in Dentistry: A Narrative Review - Hanifah, Faza Aidah; Dian Pertiwi, Nabila; Agustantina, Titien Hary (Indonesian Journal of Dental Medicine, 2023)
Background: Pulp capping and pulpotomy are treatments for exposed pulp due to injury. Calcium hydroxide is the gold standard material in pulp capping and pulpotomy because it stimulates reparative dentin formation in exposed pulp. Calcium hydroxide has the disadvantage of causing chronic inflammation, cell necrosis, the formation of tunnel defects, and weak antibacterial properties against certain bacteria. Epigallocatechin-3-gallate (EGCG) is the main catechin component of green tea and has potent anti-inflammatory and antibacterial properties against both gram-negative and positive bacteria. The addition of EGCG to calcium hydroxide has the potential to prevent chronic inflammation and improve the antibacterial properties of calcium hydroxide. Purpose: This review aims to explain the potential of the combination of calcium hydroxide and EGCG in dentistry. Review(s): EGCG has potent anti-inflammatory and antibacterial effects against Enterococcus faecalis. The addition of EGCG to calcium hydroxide has the potential to reduce the inflammatory effect and improve the antibacterial properties of calcium hydroxide. Conclusion: This review concludes that the combination of calcium hydroxide and EGCG has the potential to reduce the inflammatory effect and promote the antibacterial effect of calcium hydroxide. Further research is needed to prove the potential of the combination of calcium hydroxide and EGCG in dentistry as a material for pulp capping and pulpotomy.